2023
DOI: 10.3389/fpsyt.2023.1215807
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of metformin on cognitive and other symptom dimensions in patients with schizophrenia and antipsychotic-induced weight gain: a systematic review, meta-analysis, and meta-regression

Vera Battini,
Giovanna Cirnigliaro,
Rodolfo Leuzzi
et al.

Abstract: IntroductionMetformin has shown good efficacy in the management of antipsychotic-induced metabolic syndrome (MetS) in patients with schizophrenia or schizoaffective disorders. Its ability to induce antidepressant behavioural effects and improve cognitive functions has also been investigated: yet information has not been systematized. The aim of this study was therefore to investigate the effects of metformin on cognitive and other symptom dimension in schizophrenic patients treated with antipsychotics through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
2
4
0
Order By: Relevance
“…This implies a potential overlap in therapeutic targets between schizophrenia and T2DM, which could lead to a reassessment of treatment strategies for these patients. Previous randomised-controlled trials (RCTs) confirmed the efficacy of metformin in contrasting antipsychotic-induced metabolic side effects in individuals with psychoses (Agarwal et al, 2021;de Silva et al, 2016), while improving psychiatric and cognitive symptoms in the same population (Battini et al, 2023). Another finding of this study was the identification of significant colocalisation signals.…”
Section: Discussionsupporting
confidence: 67%
“…This implies a potential overlap in therapeutic targets between schizophrenia and T2DM, which could lead to a reassessment of treatment strategies for these patients. Previous randomised-controlled trials (RCTs) confirmed the efficacy of metformin in contrasting antipsychotic-induced metabolic side effects in individuals with psychoses (Agarwal et al, 2021;de Silva et al, 2016), while improving psychiatric and cognitive symptoms in the same population (Battini et al, 2023). Another finding of this study was the identification of significant colocalisation signals.…”
Section: Discussionsupporting
confidence: 67%
“…This study once again provided compelling clinical evidence for the efficacy of metformin in reducing prolactin. Additionally, clinical evidence suggests that metformin, while improving antipsychotic-induced metabolic syndrome in patients with schizophrenia, also has a role in improving psychiatric and cognitive symptoms ( 38 ). This indicates that the benefits of metformin for patients may be multidimensional and worth exploring further.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis suggests that metformin may enhance cognitive function in diabetic patients, potentially treating mild cognitive impairment and Alzheimer's disease, although its use for dementia prevention in older non-diabetic adults is not currently recommended, according to the study [193].…”
Section: The Winding Path From Neuroprotective Mechanisms To Proving ...mentioning
confidence: 99%